2019
DOI: 10.3892/mco.2019.1819
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary malignancies of six organs in a Japanese male patient: A case report

Abstract: As a result of recent advances in diagnostic techniques and treatment modalities, the number of patients diagnosed with multiple primary malignancies has been increasing. We report the case of a 79-year-old male with multiple primary malignancies of three histological types in six different organs: Stomach, prostate, colon, urinary bladder, facial skin and pancreas, in chronological order. The first malignancy was upper gastric cancer diagnosed in 1998. The second and third malignancies were prostate cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…15,16 Translocations in chromosome 17 and at the p53 locus may contribute to secondary cancer in colorectal cancer. 17 Yun et al 14 reported that secondary cancers occur with relatively high frequency in colorectal cancer patients and proposed that MSI might be a useful predictive marker. Interestingly, Kim et al 18 proposed that p53 and MSI are not useful markers for predicting colorectal cancer in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Translocations in chromosome 17 and at the p53 locus may contribute to secondary cancer in colorectal cancer. 17 Yun et al 14 reported that secondary cancers occur with relatively high frequency in colorectal cancer patients and proposed that MSI might be a useful predictive marker. Interestingly, Kim et al 18 proposed that p53 and MSI are not useful markers for predicting colorectal cancer in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nhiều bệnh ung thư nguyên phát trên cùng một bệnh nhân được được miêu tả lần đầu tiên bởi Billroth năm 1889 và sau đó đã được Warren và Gates đề xuất các tiêu chí chẩn đoán vào năm 1932 [1][2][3] . Nhiều bệnh ung thư nguyên phát trên cùng một bệnh nhân được định nghĩa là có nhiều *Trung tâm phẫu thuật Tim mạch -Lồng ngực -Bệnh viện hữu nghị Việt Đức **Đại học Y Hà Nội Chịu trách nhiệm chính: Phạm Hữu Lư Email: phamhuulu@hmu.edu.vn Ngày nhận bài: 26.10.2021 Ngày phản biện khoa học: 22.12.2021 Ngày duyệt bài: 30.12.2021 hơn một khối u ác tính nguyên phát có nguồn gốc mô học khác nhau xuất hiện trên cùng một bệnh nhân.…”
Section: đặT Vấn đềunclassified
“…Loại hình thương tổn này thường không phổ biến trong thực hành lâm sàng. Dựa trên các tiêu chí được đề xuất bởi Warren và Gates, chẩn đoán nhiều ung thư nguyên phát trên cùng một bệnh nhân bao gồm những đặc điểm sau [3][4][5][6] : (i) Tổn thương ác tính của từng loại khối u phải được xác định bằng mô bệnh học; (ii) Mỗi loại u ác tính xảy ra ở các vùng hoặc cơ quan khác nhau; (iii) phải loại trừ khả năng mắc bệnh ung thư ác tính thứ hai là di căn của bệnh ung thư ác tính thứ nhất. Hiện nay, với các tiến bộ trong chẩn đoán và điều trị ung thư đã làm cải thiện đáng kể thời gian sống thêm của từng bệnh lý ung thư cơ quan nhưng vấn đề tiếp cận chẩn đoán cũng như điều trị vẫn còn là một thách thức trong y học 2,5,7,8 .…”
Section: đặT Vấn đềunclassified
See 1 more Smart Citation
“…However, there are two special conditions that should be underlined: (i) systemic cancers that could potentially involve many organs should be regarded as one, and (ii) cancers with different histology should be counted as multiple cancers, regardless of whether their sites are the same and whether the diagnoses are simultaneous (1). The prevalence of MPMs varies from 0.734 to 11.7% because of differences in geography and diagnostic approaches (2,3). Epidemiological studies have shown that MPMs occur in the endometrium and ovary in 5% of women with endometrial cancer and in 10% of women with ovarian cancer, that the rate is 3.4% in patients with gastric cancer (GC), and that the other most common primary malignancy is colorectal cancer (20.4%) (4).…”
Section: Introductionmentioning
confidence: 99%